REBIRTH OF AMERICAN LITERARY THEORY AND CRITICISM : scholars discuss intellectual origins and ... turning points. - VEESER, H. ARAM (Anthem symplokē studies in theory., 2021)
A group of homogeneous interviews with contemporary literary and cultural theorists All the interviews are completed. The same ten questions were addressed to all the interviewees. The result is a homogeneous volume unlike most other interview projects.